Play Nicely: Evaluation of a Brief Intervention to Reduce Physical Punishment and the Beliefs That Justify It - Danna Valentina Nuñez-Talero; Martha Rocío González; Angela Trujillo (MDPI AG, 2024)
The objective of this study was to assess the efficacy of the Play Nicely brief intervention in diminishing both the utilization of physical punishment and the beliefs that endorse such behavior among a sample of Colombian parents with children aged 2 to 6. Utilizing a quasi-experimental design, the research included pretest and posttest evaluations and involved both an intervention group (n = 37) and a control group (n = 29). The assessment tools used were a scale to measure beliefs about the positive impacts of physical punishment and the Physical Assault subscale of the Spanish version of the Conflict Tactics Scale Parent-Child (CTSPC). Parents participated in a single online session, which offered eight interactive options and lasted 10 min. The results highlighted a high prevalence of physical punishment within the sample (81.8%) and established statistically significant correlations between the justification of physical punishment and its actual use. Approximately one month following the intervention, there was a significant reduction in the employment of physical punishment among the intervention group (p = 0.009), and a notable decrease in the belief that "Punishment is the best alternative to control children's behavior" (p = 0.010) was observed. Consequently, the Play Nicely intervention proved effective in curtailing the use of physical punishment among parents of young children, demonstrating both efficacy and cost-effectiveness within a brief timeframe.